2014
DOI: 10.1371/journal.pone.0098103
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Diversity of Strains of Enteroaggregative Escherichia coli Isolated from Cases Associated with a Large Multi-Pathogen Foodborne Outbreak in the UK

Abstract: Following a large outbreak of foodborne gastrointestinal (GI) disease, a multiplex PCR approach was used retrospectively to investigate faecal specimens from 88 of the 413 reported cases. Gene targets from a range of bacterial GI pathogens were detected, including Salmonella species, Shigella species and Shiga toxin-producing Escherichia coli, with the majority (75%) of faecal specimens being PCR positive for aggR associated with the Enteroaggregative E. coli (EAEC) group. The 20 isolates of EAEC recovered fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
2
47
0
3
Order By: Relevance
“…In the present study, which was carried out for the first time in south east Iran, we demonstrated the importance of specific virulence genes in the biofilm formation of EAEC isolates. The rate of EAEC infection, in our case, was similar with reports from other parts of Iran (23,24). Indeed, the varying presence of the different virulence factors indicates heterogeneity of the EAEC isolates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, which was carried out for the first time in south east Iran, we demonstrated the importance of specific virulence genes in the biofilm formation of EAEC isolates. The rate of EAEC infection, in our case, was similar with reports from other parts of Iran (23,24). Indeed, the varying presence of the different virulence factors indicates heterogeneity of the EAEC isolates.…”
Section: Discussionsupporting
confidence: 90%
“…The EAEC strains are heterogeneous, both with respect to symptoms developed by infected hosts and with respect to virulence genes (24). In the present study, which was carried out for the first time in south east Iran, we demonstrated the importance of specific virulence genes in the biofilm formation of EAEC isolates.…”
Section: Discussionsupporting
confidence: 54%
“…PCR assay with E coli clinical isolate C338-14 and BLAST analysis revealed an uncharacterized gene, agg5A, whose sequence has been deposited in GenBank (AB571097, AB571098) and which was mentioned in three recent studies (27,41,42). However, as of this writing no experimental characterization of this gene is available.…”
Section: Figmentioning
confidence: 97%
“…These typing schemes are instrumental in facilitating both the detection and investigation of outbreaks (4)(5)(6). Recently, whole-genome sequencing (WGS) has also been evaluated at PHE for its utility in informing outbreak investigation and surveillance of gastrointestinal disease (7)(8)(9).…”
mentioning
confidence: 99%